Long-segment spinal cord infarction complicated with multiple cerebral infarctions: a case report - Weifang Xing; Wensheng Zhang; Guozhong Ma; Guofen Ma; Jinzhao He (BMC Neurology, 2022)
Abstract Background Spinal cord infarction is a rare disorder, constituting only 1% to 2% of all neurological vascular emergencies (making it less frequent than ischaemic brain injury); however, it is severe. A case of long-segment spinal cord infarction complicated with multiple cerebral infarctions has not been reported to date. Case presentation Here, we describe one such case: a patient with spinal cord infarction from the cervical 7 (C7) to thoracic 6 (T6) vertebrae, along with anterior spinal artery syndrome and complicated by multiple cerebral infarctions. A 65-year-old farmer experienced sudden onset of severe pain in his chest, back and upper limbs while unloading heavy objects. Subsequently, both his lower limbs became weak and hypoaesthetic, and he was unable to walk. Spinal magnetic resonance imaging (MRI) revealed equal T1 and long T2 signals centred on the anterior horn of the spinal cord. The axial slice of these signals was shaped like an owl’s eye. After receiving drug treatment and active rehabilitation treatment, the patient’s ability to walk was restored. Conclusions Long-segment spinal cord infarction is rare and can be complicated with cerebral infarction. The specific aetiology is worth exploring.